Pendampingan Sertifikasi Halal Pelaku UMKM di Desa Randuagung, Kecamatan Sumberjambe, Kabupaten Jember - Awaliya Safithri; Safiroh Adania; Selfin Nabila; Silviah Taubatan Nasuha; Siska Nur Azizah; Rosidah Rosidah; Rizkiana Amalia; Diah Muharrifah; Putri Anisah; Nur Aini; Qoidul Khoir; Saini Saini (Universitas Respati Indonesia, 2026)
This study aims to describe the process of halal certification assistance for Micro, Small, and Medium Enterprises (MSMEs) in Randuagung Village, Sumber Jambe District, Jember Regency. The background of this research is the importance of halal certification as a guarantee of product compliance with Islamic law and as an effort to enhance the competitiveness of MSMEs in both local and global markets. A qualitative method with a field study approach was applied through observation, interviews, and documentation. The findings reveal that most MSME actors initially lacked knowledge about the benefits, procedures, and requirements of halal certification. Through socialization and mentoring activities, five out of nine MSMEs expressed their willingness to apply for halal certification and successfully completed the administrative requirements, including the issuance of a Business Identification Number (NIB). Beyond administrative aspects, the mentoring program also increased the awareness of MSMEs regarding the importance of maintaining standards of hygiene, halal integrity, and food safety. This program not only adds value to MSME products but also supports government initiatives in developing the halal industry and contributes to empowering rural communities’ economy. For sustainability, further technical guidance is needed to ensure that all MSMEs are able to complete the halal certification process independently.